2020
DOI: 10.1080/1331677x.2020.1820359
|View full text |Cite
|
Sign up to set email alerts
|

International diversification, ownership structure and performance in an emerging market: evidence from Chile

Abstract: This research analyzes the impact of international diversification on the performance of Chilean exporting firms. Considering a sample of 47 companies listed on the Santiago Stock Exchange during the period 2003-2013, we found an international diversification discount. Secondly, when investigating the relationship between international diversification and performance, we found that they are related through an inverted U curve. Finally, we investigated how the ownership structure moderates the relationship betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 113 publications
(145 reference statements)
1
2
0
Order By: Relevance
“…This research indicates that CEI moderated by the structure of publicly owned share ownership have a significant positive influence on the company's market performance. This is in line with the studies by Bjuggren et al (2007) andEspinosa-Méndez et al (2021). In addition, the results of this study are in line with the findings of Gungoraydinoglu and Öztekin (2011), Degryse et al (2012), Detthamrong et al (2017), Ramli et al (2019), andTsegba &Achua (2011), which prove that capital structure has a positive effect on company performance.…”
Section: The Influence Of Corporate Ethical Identity and The Structur...supporting
confidence: 92%
“…This research indicates that CEI moderated by the structure of publicly owned share ownership have a significant positive influence on the company's market performance. This is in line with the studies by Bjuggren et al (2007) andEspinosa-Méndez et al (2021). In addition, the results of this study are in line with the findings of Gungoraydinoglu and Öztekin (2011), Degryse et al (2012), Detthamrong et al (2017), Ramli et al (2019), andTsegba &Achua (2011), which prove that capital structure has a positive effect on company performance.…”
Section: The Influence Of Corporate Ethical Identity and The Structur...supporting
confidence: 92%
“…According to Cheng and Yang (2017), economic value is added as one of the financial indicators, which allows the management and the other stakeholders to assess the extent of the bank's performance over time based on the real economic earnings income of the bank. Christian et al (2021) reported that economic value-added has been used extensively in the literature as one of the financial indicators of the extent of economic value-added to the residual wealth of an organization. According to Clinton and Salami (2021), value-added economic measures revealed management competence and financial performance based on their residual income.…”
Section: Conceptual Reviewmentioning
confidence: 99%
“…It entails strategic asset seeking, market seeking, and expansion of banking operations on an international landscape in search of international new clients while servicing existing clients in international transactions. Christian et al (2021) revealed that internationalization plays a significant role in impacting the financial stability of banks, and the banks' desire for more sophisticated technologies and advanced infrastructures superior to domestic infrastructural decays in Nigeria.…”
Section: Introductionmentioning
confidence: 99%